Środki obrony przed egzekucją administracyjną – uwagi na tle nowelizacji ustawy o postępowaniu egzekucyjnym w administracji - Sobieralski, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The aim of this paper is to classify remedies against administrative enforcement. Legal science differentiates between means of appeal against enforcement proceedings performed in administrative procedure and those performed in judicial procedure. When discussing protection from administrative enforcement it is vital to distinguish between means of defence on the substance, which aim at fighting with the validity or admissibility of administrative enforcement, and means of formal defence aiming at the provision of legitimate conduct of the enforcement procedure. In this paper the author assumes that both substantial and formal remedies against enforcement may be undertaken in administrative and judicial procedures. Distinguishing remedies on the substance against administrative enforcement is crucial from the point of view of protecting rights of the individual from public administrative authorities’ imperious intervention, as well as due to the need to protect the objective legal system in the country. For these remedies refer to the existence and enforceability of the monetary and non-monetary public-law duty, which is the basic subject of administrative enforcement proceedings, even though it is located externally to them. In the paper it has been emphasized that the amendments to the Act on the Enforcement Proceedings in Administration carried out between 2013 and 2016 have attempted to regulate in a more complex way legal consequences of the indebted taking advantage of all formal and substantial remedies against administrative proceedings. In the paper the legal analysis methodology was used.
Keywords: verification of decision; the indebted; complaint against enforcement proceedings; amendment; defence against enforcement; allegation; remedies; public-law duty; administrative court; administrative enforcement; creditor; enforcement authority